Rumah Imun dan Ambulan Motor sebagai Upaya Pencegahan Stunting dan Sarana Kegawatdaruratan di Desa Pagung Kabupaten Kediri - Sulisetyawati, Theresia Indah Budhy; Roestamadji, Retno Indrawati; Megasari, Ni Luh Ayu; Imannia, Ristya Sylva; Wardhani, Renita Gusti; Maulanasari, Ersa Afifah; Cheardi, Natallensi Deara; Buana, Dwi Candra (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
This community service aims to improve the skills and knowledge of the surrounding community as well as first aid accommodation to health service facilities in the community of Pagung Village, Semen District, Kediri Regency, East Java. The implementation method of this community service is a field survey to identify stunting problems, making pocket books on emergencies and stunting, making motorbike ambulances (LANTOR) to facilitate access to health services, and counseling related to emergencies, balanced nutrition, and stunting. The results of this community service show that counseling and training related to first aid and emergencies can improve the knowledge and skills of the community in Pagung Village, in addition, the provision of "LANTOR" can facilitate and smooth community mobility to the nearest health service facilities.